A Potent and Orally Active Antagonist (SM-406/AT-406) of Multiple Inhibitor of Apoptosis Proteins (IAPs) in Clinical Development for Cancer Treatment - Cai, Qian; Sun, Haiying; Peng, Yuefeng; Lu, Jianfeng; Nikolovska-Coleska, Zaneta; McEachern, Donna; Liu, Liu; Qiu, Su; Yang, Chao-Yie; Miller, Rebecca; Yi, Han; Zhang, Tao; et al. (Journal of medicinal chemistry, 2011)
We report the discovery and characterization of SM-406 (compound 2), a potent and orally bioavailable Smac mimetic and an antagonist of the inhibitor of apoptosis proteins (IAPs). This compound binds to XIAP, cIAP1, and cIAP2 proteins with K i of 66.4, 1.9, and 5.1 nM, respectively. Compound 2 effectively antagonizes XIAP BIR3 protein in a cell-free functional assay, induces rapid degradation of cellular cIAP1 protein, and inhibits cancer cell growth in various human cancer cell lines. It has good oral bioavailability in mice, rats, non-human primates, and dogs, is highly effective in induction of apoptosis in xenograft tumors, and is capable of complete inhibition of tumor growth. Compound 2 is currently in phase I clinical trials for the treatment of human cancer.